Arabidopsis PCaP2 Functions as a Linker Between ABA and SA Signals in Plant Water Deficit Tolerance - Wang, Xianling; Wang, Yu; Wang, Lu; Liu, Huan; Zhang, Bing; Cao, Qijiang; Liu, Xinyu; Bi, Shuangtian; Lv, Yanling; Wang, Qiuyang; Zhang, Shaobin; He, Ming; et al. (Frontiers in Plant Science, 2018)
Abstract Water stress has a major influence on plant growth, development, and productivity. However, the cross-talk networks involved in drought tolerance are not well understood. Arabidopsis PCaP2 is a plasma membrane-associated Ca2+-binding protein. In this study, we employ qRT-PCR and β-glucuronidase (GUS) histochemical staining to demonstrate that PCaP2 expression was strongly induced in roots, cotyledons, true leaves, lateral roots, and whole plants under water deficit conditions. Compared with the wild type (WT) plants, PCaP2-overexpressing (PCaP2-OE) plants displayed enhanced water deficit tolerance in terms of seed germination, seedling growth, and plant survival status. On the contrary, PCaP2 mutation and reduction via PCaP2-RNAi rendered plants more sensitive to water deficit. Furthermore, PCaP2-RNAi and pcap2 seedlings showed shorter root hairs and lower relative water content compared to WT under normal conditions and these phenotypes were exacerbated under water deficit. Additionally, the expression of PCaP2 was strongly induced by exogenous ABA and SA treatments. PCaP2-OE plants showed insensitive to exogenous ABA and SA treatments, in contrast to the susceptible phenotypes of pcap2 and PCaP2-RNAi. It is well-known that SNF1-related kinase 2s (SnRK2s) and pathogenesis-related (PRs) are major factors that influence plant drought tolerance by ABA- and SA- mediated pathways, respectively. Interestingly, PCaP2 positively regulated the expression of drought-inducible genes (RD29A, KIN1 and KIN2), ABA-mediated drought responsive genes (SnRK2.2, -2.3, -2.6, ABF1, -2, -3, -4), and SA-mediated drought responsive genes (PR1, -2, -5) under water deficit, ABA or SA treatments. Taken together, our results showed that PCaP2 plays an important and positive role in Arabidopsis water deficit tolerance by involving in response to both ABA and SA signals and regulating root hair growth. This study provides novel insights into the underlying cross-talk mechanisms of plants in response to water deficit stress.